La movilización estudiantil del profesorado por la renovación de sus planes de estudio durante la última transición hacia la democracia en Argentina (1984-1988) - Ramos Gonzales, Josefina (Anuario de Historia de América Latina, 2025)
This article examines the impact of student mobilization on the renewal of the formative experience of teacher-education students during Argentina’s most recent transition to democracy. Drawing on a multiple empirical base, it reveals the challenges posed by this segment of the student body to several features of their academic training and analyzes how these demands intersected with the political conflict and educational policies of the period. First, the article focuses on the years of the so-called post-dictatorship, reconstructing the claims aimed at questioning the perspectives, tendencies, and training modalities inherited from the previous period—particularly the demand to revoke the curricula imposed in 1982 by Minister of Education Cayetano A. Licciardo during the last de facto civil-military dictatorship. Second, it examines the student responses, during the more advanced stage of the Alfonsín administration, to two pedagogical innovations proposed by the newly created National Directorate of Higher Education (DINES): the modalities of student participation linked to the MEB curriculum and the implementation of non-mandatory final examinations—both of which elicited opposition as well as alternative proposals.The article concludes by reflecting on how student mobilization shaped the tempo and specific contours of the educational policies targeting the sector in a region still marked by Operation Condor, where a trend toward the marketization of Higher Education was beginning to crystallize.
Keywords: Student mobilization; Educational Reform; Higher Teacher Training Institutes; transition to democracy in Argentina